CANDI RETNO SEBAGAI SUMBER BELAJAR SEJARAH AGAMA HINDU - Naufal Raffi Arrazaq (Guna Widya: Jurnal Pendidikan Hindu, 2023)
The study of the potential use of archaeological remains in Candi Retno as a source of learning the history of Hinduism during the Mataram Kuno Kingdom has not been carried out in depth. The purpose of this study is to analyze a variety of archaeological findings patterned Hindu during the Mataram Kuno Kingdom at Candi Retno. Another objective is to analyze the potential development of Hindu-style archaeological relics in Candi Retno as a source of learning the history of Hinduism during the Mataram Kuno Kingdom. Qualitative methods were used in this study which aimed to analyze the object of study, namely archaeological relics in Candi Retno in the form of temples and yoni. The results showed that the variety of archaeological remains found at Candi Retno were temple building ruins, yoni and some artifacts in the form of loose finds. The findings of archaeological remains at Candi Retno show that in the past the people of the Mataram Kuno Kingdom embraced Hinduism. Archaeological relics with Hindu patterns in Candi Retno have the potential to be developed as a source of learning Hindu history in historical learning. The material that can be developed is the history of Hinduism during the Mataram Kuno Kingdom, the iconography of Hinduism during Mataram Kuno, the technology of building sacred Hindu buildings, and the preservation of archaeological relics with a Hindu background.